Development and evaluation of niobium and molybdenum substituted magnetite catalysts for fenton-like treatment of recalcitrant wastewaters / Shima Rahim Pouran - Shima, Rahim Pouran (2016)

(untitled)
Iron oxides are conventionally used as heterogeneous Fenton catalysts because of their abundance, ease of separation, affordability, and applicability in broad pH range. This is especially reported for magnetite due to the presence of Fe2+ cations in its structure. However, the magnetite-catalyzed Fenton reaction has lower reaction rate compared with the homogeneous reaction, which led to the introduction of transition metal-substituted magnetites. Previous studies focused mainly on the fourth series transition metals of the periodic table, and there have not been any comprehensive study on the effects of the transition metals from period five on the structure and activity of magnetite in Fenton process. Therefore, the present study synthesized a series of single, and co-doped niobium and/or molybdenum substituted magnetites by co-precipitation method prior to characterization. The amount of Nb and Mo incorporated in the samples were: Fe3-xNbxO4 (x = 0.022, 0.049, 0.099, and 0.19), Fe3-xMoxO4 (x = 0.028, 0.069, 0.13, and 0.21) and Fe3-x-yNbxMoyO4 (x = 0.025, 0.049, 0.099, 0.149, and 0.171; y = 0.094, 0.089, 0.073, 0.032, and 0.023). All samples maintained the inverse spinel structure and magnetic property. The imported Nb4+ and Mo4+ mainly replaced the octahedral Fe3+ and Fe2+ cations, respectively. Higher Nb and Mo content decreased the crystal size significantly with concomittant increase in specific surface area, resulting in higher adsorption capacity of the catalysts. Subsequently, the activity of the synthesized samples was tested through the Fenton-like reaction for degradation of a model wastewater (methylene blue solution, MB). The presence of transition metals significantly improved the degradation of MB, especially with higher Nb and Mo contents in which, complete MB removal was achieved within 180 min. This could be attributed to a combination of factors: (i) increased adsorption capacity of the samples evidenced by larger surface area; (ii) participation of thermodynamically favorable Nb4+/Nb5+ and Mo4+/Mo6+ redox pairs iv in regeneration of Fe2+ and •OH radical generation, (iii) presence of oxygen vacancies serves as active sites on the surface of the catalysts, and (iv) direct involvement of peroxo-niobium complexes in MB degradation. Three catalysts, Fe2.79Nb0.19O4, Fe2.79Mo0.13O4 and Fe2.79Nb0.171Mo0.023O4, with the highest activity in the Fenton reaction were chosen, and used for treatment of MB and methyl orange (MO) solutions through the Fenton-like, UV/Fenton-like and US/Fenton-like reactions. The incorporated Nb and Mo significantly accelerated MB degradation in the US/Fenton followed by the UV-B/Fenton and UV-A/Fenton reactions. However, UV-B/Fenton reaction was more effective in degrading MO compared to the other oxidation systems. Furthermore, MB adsorption on the surface of the samples was well described by pseudo-second-order model kinetics. In addition, MB oxidation through the Fenton reaction catalyzed by the Fe3-xNbxO4, Fe3-xMoxO4, and Fe3-x-yNbxMoyO4 samples was well described by the pseudo-first-order, zero-order, and pseudo-first-order kinetics, respectively. The amount of leached iron and incorporated transition metals were not significant in acidic condition and undetectable in neutral and basic solutions. The samples retained their catalytic efficiency after three recycles in Fenton process. The results proved that niobium and molybdenum substituted magnetites enhanced the Fenton oxidation of organic pollutants. Therefore this highlights the promising potentials for treating recalcitrant effluents